2018
DOI: 10.1007/s12603-018-1006-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Intake and Overall Diet Quality are Associated with Handgrip Strength in African American and White Adults

Abstract: ObjectiveTo determine the association of handgrip strength (HS) with protein intake, diet quality, and nutritional and cardiovascular biomarkers in African American and White adults.DesignCross-sectional wave 3 (2009–2013) of the cohort Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study.ParticipantsSocioeconomically diverse urban population of 2,468 persons aged 33 to 71 years.MeasurementsSocio-demographic correlates, dietary intakes and biomarkers, HS, physical performance measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 63 publications
5
17
1
2
Order By: Relevance
“…Therefore, this pattern of sarcopenia might be different from the one we studied in the current study and their findings cannot easily be generalized to other healthy populations. Unlike our findings, a cross-sectional study indicated a favorable association between adherence to the DASH diet and handgrip strength, as a component of sarcopenia 32 . In a quasi-experimental study, combined resistance training (RT) along with a counseling on modified DASH diet in 95 overweight and obese older adults aged 55 to 80 years resulted in significant improvements in muscle strength, as measured by handgrip strength and knee extensor torque 33 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, this pattern of sarcopenia might be different from the one we studied in the current study and their findings cannot easily be generalized to other healthy populations. Unlike our findings, a cross-sectional study indicated a favorable association between adherence to the DASH diet and handgrip strength, as a component of sarcopenia 32 . In a quasi-experimental study, combined resistance training (RT) along with a counseling on modified DASH diet in 95 overweight and obese older adults aged 55 to 80 years resulted in significant improvements in muscle strength, as measured by handgrip strength and knee extensor torque 33 .…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, DASH diet may reduce the risk of age-related chronic conditions (e.g., cardiovascular diseases, diabetes and cancer), that are associated with worsening muscle health 12,14,[28][29][30][31] . We are aware of only two studies that examined the link between DASH diet and sarcopenia or its components 32,33 . Adherence to this eating style in African American and White adults was associated with better handgrip strength (HS), which is a simple and reliable method to evaluate muscle function 32 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most commonly applied and reliable assessment methods for this purpose is 24-h dietary recall, which constitutes a logical approach to examining the nutrients that influence muscle strength and the underlying mechanisms, because it captures actual food consumption. In addition, recent studies imply that HGS can be used as a predictor of nutritional status [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%